Profil produk pelancongan makanan dalam mempertingkatkan kualiti pengalaman pelancong di "World Heritage Site" - Rahim, Rohainis (2010)
Food is a basic need for every human including tourist that visit to tourism destination. This study about food tourism product profile in enhancing tourist quality in experience at World Heritage Site as development of tourism industry catalyst food around Bandar Hilir, Malacca. Tourism industry give interest to food tourism as part of experience when vacation because that sensual, symbolic and mean to tourists. Issue of this study is not having researcher study food as a puli or visit motivation to tourism destination. Local organization's failure drop make heavier food tourism aspects and menu privilege cooking / food that are made up various cthnic / local cultures not suggested as one local identity. This research to identify category of local food tourism from various ethnic / culture based on model 'importance of a special interest in food' (Hall and Liz Sharpies, 2003), tourism group category (Enteleca research & Consultancy, 2000) and motivation visiting (C. Micheai Hall, 2003). Analysis involving qualitative method and quantitative in measure study variables and application quantitative software such as SPSS 16 (Statistical Package for The Social Science) is used. Research finding is category and level of food tourist characteristic in this study area. The decision show Chinese food staying at levels / tourism category gastronomy namely *high interest' from group 'food tourist' and Indian food at levels ’low interest / no' where highest percentage that have tourist uninterested to be trying or buy that India food product. As a results, this study to help action and tourism development planning food capable of carrying out according to level that identified in study area.